Neurosurgical Aspects of Brain Trauma in Children - Benedek, Pedro; Grille, Pedro (Cirugía del Uruguay, 1978)
A series of 193 children with craníocerebral trauma treated at the Instituto de Neurología, Montevideo, from 1971 to 1975 is presented. The morbidity, mortality, biomechanics, pathology and physiopathology, the clinical and neuroradiological features and the neurosurgical treatment are described.